(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Abstract: Integrity and Freedom of Conscience as Divine Gifts Sometimes people with a Christian education background came across certain temptation or opportunities which seem to require different ways of behaving comparing them to what they had known and had been convinced of. Gradually their style of life change and their attitude towards Christian principles becomes one of skipping not keeping. Even though they look good in outside, in their inner being the voice of their conscience cries to them and do not give them the real innerpeace they long for. Such people struggle with the question of whether integrity and freedom of conscience are not in opposition to each other and as a result they are somehow caught in between. There is a continuous fight between the principles of God planted into one’s mind from the creation and the temptation of doing what one wants with his or her life. Returning to Jesus they knew, becomes the way of liberation and rehabilitation as the Scripture shows by the encounter between Zacchaeus and Jesus.